Đặt xy=a ,\(x^2+y^2\)=b pt trên trở thành
\(\left\{{}\begin{matrix}a^2-a-2=0\\b=a^2\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}\left[{}\begin{matrix}a_1=2\\a_2=-1\end{matrix}\right.\\\left[{}\begin{matrix}b_1=4\\b_2=1\end{matrix}\right.\end{matrix}\right.\)
ta có 4 trường hợp sau
th1 xy=2;\(x^2+y^2=4\)ta có hệ
\(\left\{{}\begin{matrix}xy=2\\x^2+y^2=4\end{matrix}\right.\)hệ pt trên có 2 nghiệm (\(\sqrt{2};\sqrt{2}\)),(\(-\sqrt{2};-\sqrt{2}\))(1)
th2 xy=2;\(^{x^2+y^2=1}\)ta có hệ
\(\left\{{}\begin{matrix}xy=2\\x^2+y^2=1\end{matrix}\right.\)hệ pt vô nghiệm
th3\(\left\{{}\begin{matrix}xy=-1\\x^2+y^2=4\end{matrix}\right.\)hệ pt có 2 nghiệm (\(\dfrac{\sqrt{6}+\sqrt{2}}{2};\dfrac{-\sqrt{6}+\sqrt{2}}{2}\)),(\(\dfrac{\sqrt{6}-\sqrt{2}}{2};\dfrac{-\sqrt{6}-\sqrt{2}}{2}\))(2)
th4\(\left\{{}\begin{matrix}xy=-1\\x^2+y^2=1\end{matrix}\right.\)hệ pt vô nghiệm
từ (1) và(2) suy ra hệ pt trên có 4 nghiệm (-\(\sqrt{2};-\sqrt{2}\)),(\(\sqrt{2};\sqrt{2}\)),(\(\dfrac{\sqrt{6}+\sqrt{2}}{2};\dfrac{-\sqrt{6}+\sqrt{2}}{2}\)),(\(\dfrac{\sqrt{6}-\sqrt{2}}{2};\dfrac{-\sqrt{6}-\sqrt{2}}{2}\))